Four-Tier Comparative Analysis and Contribution Attribution. - Kewei Wang (556371) (2025)
(A) Multi-dimensional performance across four optimization strategies (A: Current System, B: Standard Bi-level, C: Advanced Algorithms, D: Our Method). Bars represent mean values (n = 30) with error bars indicating standard deviation. (B) Contribution attribution of the total impact. Based on Shapley value decomposition, separating the effects of System Architecture (Restructuring), Algorithm Enhancement, and Process Integration (Our Enhancements).